2016
DOI: 10.18203/issn.0019-5359.indianjmedsci20163532
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Disintegrin and Metalloprotease 33 Gene Polymorphisms and Their Haplotypes With Asthma in the North‑indian Population

Abstract: AIMS, SETTINGS, AND DESIGN:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The study of Su et al [60] (China) observed that patients with the rs2280091 (T1) genotype AG had 3.19 greater odds and those with the genotype GG 8.28 greater odds of suffering from asthma. Awasthi et al [61] (India) observed a weaker association, with the rs2280091 (T1) genotype AG having 1.6 greater odds and the genotype GG 2.8 greater odds of suffering asthma. For the ADAM33 SNP rs2787094 (V4), Su et al [60] (China) observed that patients with the CG and GG genotypes had 2.82 and 10.28 greater odds of suffering asthma.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The study of Su et al [60] (China) observed that patients with the rs2280091 (T1) genotype AG had 3.19 greater odds and those with the genotype GG 8.28 greater odds of suffering from asthma. Awasthi et al [61] (India) observed a weaker association, with the rs2280091 (T1) genotype AG having 1.6 greater odds and the genotype GG 2.8 greater odds of suffering asthma. For the ADAM33 SNP rs2787094 (V4), Su et al [60] (China) observed that patients with the CG and GG genotypes had 2.82 and 10.28 greater odds of suffering asthma.…”
Section: Discussionmentioning
confidence: 97%
“…Xue et al [64] (China) and Tripathi et al, [59] (India) observed 1.91 and 3.3 higher odds for the GG genotype, but the CG genotype was not significantly associated with asthma. Awasthi et al [61] (India) observed that patients with the ADAM33 SNP rs3918396 (S1) genotypes AG and GG had a significant association with asthma, presenting 2.1 and 3.6 greater odds, respectively. For the ADAM33 SNP rs677044 (V3), Xue et al [64] (China) observed that patients with the CT and CC genotypes had 1.51 and 2.77 greater odds of suffering from asthma.…”
Section: Discussionmentioning
confidence: 99%
“…These domains impart different functions of ADAM33, which are cellcell adhesion, cell-cell and cell-matrix interactions, and cell migration. The ADAM protein family constitutes many kinds of cell-surface proteins, including receptors, cytokines, and growth factors [13]. A study by Awasthi found an association of the ADAM 33 SNPs T2, T1, and S1 with asthma.…”
Section: Advances In Health Sciences Research Volumementioning
confidence: 99%